2021
DOI: 10.1111/jocd.14632
|View full text |Cite
|
Sign up to set email alerts
|

Monophasic versus biphasic hyaluronic acid filler for correcting nasolabial folds: a systematic review and meta‐analysis

Abstract: Background: Hyaluronic acid (HA) fillers are the most popular dermal fillers for wrinkle correction and facial rejuvenation. Recently, there has been an interest toward classifying HA fillers based on the cross-linking properties into monophasic (MHA) and biphasic (BHA) fillers. We aimed to compare the efficacy and safety outcomes between MHA and BHA fillers for the correction of nasolabial folds (NLFs). Methods:We searched Medline, Embase, and CENTRAL for randomized controlled trials (RCTs) that compared MHA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…However, existing research has not found significant differences in the safety of HA with different cross-linking degrees. 39 Unfortunately, data on the cross-linking degree of HA have rarely been reported in the cases included, so this study could not compare the safety of injection under different cross-linking degrees.…”
Section: Discussionmentioning
confidence: 98%
“…However, existing research has not found significant differences in the safety of HA with different cross-linking degrees. 39 Unfortunately, data on the cross-linking degree of HA have rarely been reported in the cases included, so this study could not compare the safety of injection under different cross-linking degrees.…”
Section: Discussionmentioning
confidence: 98%
“…Their analysis revealed that the most frequent AEs were injection-related, such as tenderness, swelling, bruising, mass, and pain. Another meta-analysis evaluated the difference between monophasic vs. biphasic hyaluronic acid fillers for correcting nasolabial folds [ 23 ]. The study found injection site pain to be the main complaint after receiving dermal fillers.…”
Section: Reviewmentioning
confidence: 99%
“…Various systematic reviews and meta-analyses have been conducted to investigate the effectiveness, safety, and adverse events of dermal fillers injected into the nasolabial folds [20][21][22][23]. However, each meta-analysis is distinct in that it each evaluates certain dermal fillers.…”
Section: Previous Studies On Adverse Events Of Dermal Fillersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, sodium hyaluronate-based fillers have been widely promoted because of their good biocompatibility and reversibility and are increasingly accepted by patients owing to the minimally invasive procedure and rapid recovery [1,2]. However, the maintenance and effectiveness of filling effects remain a concern, and the filling effect may gradually weaken over time [3].…”
Section: Introductionmentioning
confidence: 99%